Transformasi Naratif Kisah Nabi Sulaiman dalam Relasi Al-Qur’an–Bible: Analisis Intertekstual Julia Kristeva - Muhammad Rasyidin; Nur Aeni Putri Gafar; Mar'atun Nabila; Dian Nur Anna; Arbain, Arbain (IAIN KENDARI, 2026)
Differences between the narratives of Prophet Solomon in the Qur’an and the Bible are often treated merely as textual variations, thereby obscuring the deeper processes of meaning transformation operating between the two scriptures. This study investigates how the Qur’an systematically reconfigures earlier biblical traditions through intertextual mechanisms. Employing qualitative textual analysis within Julia Kristeva’s intertextual framework, the study compares selected Qur’anic passages with their biblical counterparts to identify patterns of narrative transformation. The findings reveal that Qur’anic narrative transformation operates through four principal mechanisms: normative haplology, functional modification, prophetic expansion, and theological conversion. Through these mechanisms, the Qur’an reorganizes shared narrative elements and constructs new semantic structures that emphasize prophethood, monotheism, and the moral integrity of Solomon. Rather than merely revising earlier traditions, the Qur’an selectively and systematically reshapes inherited narratives in accordance with its theological worldview. This study proposes a mechanism-based model of Qur’anic intertextuality that conceptualizes narrative transformation as a structured hermeneutical process rather than an incidental textual adaptation, thereby extending Kristeva’s intertextual theory into the study of sacred texts.